2008
DOI: 10.1002/smll.200800734
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Nanodot Arrays of Transition‐Metal Oxides Fabricated by Dry Deposition Combined with a Nanoimprint‐Lithography‐Based Molybdenum Lift‐Off Technique

Abstract: On the dot: Large‐area nanodot arrays of Fe2.5Mn0.5O4 (FMO; see image), with dot sizes as small as 100 nm, can be fabricated by a Mo lift‐off technique. The FMO dots grow epitaxially on the substrate and show ferromagnetic properties. Their coercive magnetic field is identical to that of continuous FMO thin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…For example, as demonstrated by Suresh [59], the MOS capacitor incorporating ZnO arrays demonstrated a hysteresis of 2.82 V, which was much superior to the low hysteresis of ca. 0.4 V for the control substrates without ZnO structures.…”
Section: Applications Of Ceramic Nanostructures Prepared By Nilmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, as demonstrated by Suresh [59], the MOS capacitor incorporating ZnO arrays demonstrated a hysteresis of 2.82 V, which was much superior to the low hysteresis of ca. 0.4 V for the control substrates without ZnO structures.…”
Section: Applications Of Ceramic Nanostructures Prepared By Nilmentioning
confidence: 94%
“…Suzuki et al presented a method for fabricating a large-area dot array of Fe 2.5 Mn 0.5 O 4 (FMO) by a combination of pulse laser deposition (PLD), NIL, and the Mo lift-off technique [59]. In the procedure (Fig.…”
Section: Nil Involving Lift-off Processmentioning
confidence: 99%
“…Nanoimprint lithography (NIL) [6] has recently been demonstrated as an efficient tool for large-area patterning of non-epitaxial magnetic structures, with specific advantages over both photolithography and e-beam lithography [7,8]. Suzuki et al (2008) recently introduced a NIL process compatible with epitaxial film materials, in which the polymeric resist mask was transferred to a high-temperaturestable molybdenum (Mo) mask prior to metal epitaxy [9]. However, they have demonstrated this process only for very thin films of one single material, and the liftoff quality seemed to be imperfect with rough edges as revealed by scanning electron microscopy (SEM) images.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that excellent single crystalline and epitaxial nanostructures could be fabricated using this process as shown in ref 15. Furthermore, to make sure of electronic structure after the process of Mo lift-off, we have also conducted hard X-ray photoemission spectroscopy (HX-PES).…”
mentioning
confidence: 97%
“…15 NIL is a novel and low-cost nanolithography method for polymers and can be applied down to sub-10-nm regions and over large areas. 16 An amorphous Mo nanomask fabricated via the NIL process is stable at high temperatures over 300°C.…”
mentioning
confidence: 99%